Type of tiles and their application in building / Muhammad Zahid Zainol - Zainol, Muhammad Zahid (Universiti Teknologi MARA, Perak, 2019)
A tile is a thin object usually square or rectangular in shape. Tile is a manufactured piece of hard-wearing material such as ceramic, stone, metal, baked clay, or even glass, generally used for covering roofs, floors, walls, or other objects such as tabletops. Alternatively, tile can sometimes refer to similar units made from lightweight materials such as perlite, wood, and mineral wool, typically used for wall and ceiling applications. While finishes are usually used in the final part of the construction or manufacturing process, forming the final surface of an element which can protect the element from impact, water, frost, corrosion, abrasion, and or they can be decorative. Finishes commonly relate to internal surfaces, but they may also be applied to external elements. Therefore, this report will be discussed in more detail about types and uses of tile finishes. Next, to study the installation method of tile finishes. Lastly is to identify types of defects on tiles that usually occurred. This report mainly based on construction site named Residensi KepongMas, Kepong under the company Kenwingston Sdn Bhd. Residensi KepongMas refers to a reasonably priced, high-rise condominium nestled at kepong and is easily accessible via the Middle Ring Road. For this study, it is found that the main type of tile used for the case study building are ceramic tiles. Secondly, installation method requires good planning and workmanship. Lastly, defects may occur due to lack of supervision and poor workmanship.